Kosmologi Musik Rumah Siwaluh Jabu di Desa Lingga, Kabupaten Karo - Regina Cintya Arumba; Sugiyanto, Danis; Salim, Muhammad Nur; Ikhwan, Nil (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
This research is based on the awareness that music functions both as an artistic expression and as a cosmological representation embedded within the cultural structures of traditional societies. The Siwaluh Jabu traditional house in Lingga Village, North Sumatra, was selected as the object of study to examine the relationship between music and the cosmological views of the Karo people. The purpose of this study is to reveal the meaning of music within cultural practices and rituals carried out in the Siwaluh Jabu House, as well as to explore musical elements that reflect the continuity between humans, ancestors, and the universe. This research employs a qualitative approach, with data collected through literature review, participatory observation, and interviews with traditional leaders and local artists. The data analysis was conducted through data reduction, classification, data presentation, and drawing of conclusion. The results of the study show that music both the vocal mantra “ole…ah…ole” and the Gendang Lima Sendalanen ensemble contains symbolic values that interpret wood as a natural element, sustain social connections between groups, and reinforce the social system embedded in the spatial organization of the Siwaluh Jabu traditional house. Music serves as a medium of spiritual and cultural communication that unites the physical and metaphysical dimensions of life. The implications of this research enrich the perspective of music culture and emphasize the importance of preserving traditional music as a local knowledge system integrated with the cosmology of the Karo people.